True Reflections on Barron’s Reflections of Canada: “Canada 150: Music and Belonging” - Ries, Ardelle (Intersections, 2016)
Esteemed Canadian music educator John Barron (1939–2014) commissioned and edited Reflections of Canada (RofC)—a three-volume collection of 147 Canadian folk songs arranged for a cappella choirs between 1985 and 1991. Published by Frederick Harris Music, RofC contains folk songs derived from Indigenous, French, and English traditions and was considered to be a fine resource for music educators. In the late 1990s, RofC was declared out of print, with publishing rights returned to the editor, composers of the arrangements, and other copyright holders. To celebrate confederate Canada at 150 and brought back by popular demand, a two-volume second edition of RofC has been created and will be released by Cypress Music in June 2017. Through narrative and ethnographic inquiry, the factors that influenced the genesis and subsequent demise of the first edition will be discussed, followed by an examination of the process and challenges encountered in the creation of a culturally sensitive second edition that embodies a realistic reflection of twenty-first-century Canada.